Two-Way Influence Processes In Leader-Follower Dyads - Herold, David M. (Academy of Management Journal, 1977)
A laboratory experiment demonstrated that leaders' behaviors and attitudes varied as a function of subordinate performance and that subordinate behaviors and attitudes varied as a function of leaders' behavior. The effect of leader behavior on subordinate performance was shown to be conditional upon leader power. Findings are discussed in terms of their implication for leadership research.